THE EFFECTIVENESS OF COOPERATIVE LEARNING MODEL OF TGT TYPE AND NHT ON STUDENT LEARNING OUTCOMES OF GRADE VII OF SMP - Devitri Rahmawati; Nur Arina Hidayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
A conventional learning model that is still used in the mathematics learning process at school causing less active students in the class because they are just sitting, listening, and make a note when the teacher explains the lesson. This is experimental research aimed at finding out the cooperative learning model's effectiveness between type TGT (Teams Games Tournament) and NHT (Numbered Heads Together). This research population consists of 4 classes from seventh-grade students in State Junior High School 1 Turi Sleman (SMPN 1 Turi Sleman) in 2017/2018. This research uses a purposive sampling technique, where VII C and VII B as an experimental class. Instrument tests include validity tests, power differentiator tests, and reliability tests. In analyzing the data, this research uses an analysis prerequisite test consisting of a normality test and homogeneity test. The hypothesis test uses two t-tests and a one-party test. Two t-tests, with a significant level of 5% and 61 degrees of freedom, show that  and =1,99996 with the result  > . It shows that  denied and  accepted, which means there are differences in learning mathematics results in seventh-grade students of SMP Negeri 1 Turi Sleman using cooperative learning model type TGT with type NHT. Based on the calculation of a one-party t-test with a significant level of 5% and 61 degrees of freedom, it shows that  and = 1.670385 with the result > . This indicates that   is denied and  accepted, which means that cooperative learning model type TGT is more effective than type NHT reviewed by mathematics learning result of the seventh-grade students SMPN 1 Turi district Sleman in the academic year 2017/2018.